(untitled) (The Journal of Psychology and Sociology, 2016)
The article deals with post-traumatic growth occurring in parallel attempts to adjust to precarious circumstances and high levels of psychological distress. Previously it was thought that the main and almost inevitable reactions to difficult life circumstances are mental health disorders. However, in recent years, scientists have been paying increasing attention to the fact that the injury can also be a catalyst for profound positive as personal and social transformation. Positive psychological changes that have occurred since the individual who suffered severe mental trauma in the psychological literature was considered to be manifestations of the phenomenon of post-traumatic growth. Posttraumatic growth is manifested in the fact that changing the relation of man to himself, to others, changing the overall philosophy of life. As a result of overcoming traumatic situation and its impact on a person begins to feel both more vulnerable and more powerful than before. Sometimes it opens up new opportunities in life, which he had not suspected. Changing attitude to life – it is not seen as a given, granted, but as a gift, something that should be used sensibly.